Impact of Coronavirus Pandemic on the Global Economy: Demand and Supply Shocks - Chinenye Ifeoma Nwokolo; Matthew Ikechukwu Ogbuagu; Onyebuchi Iwegbu (Ovidius University Annals: Economic Sciences Series, 2020)
This paper examines the dynamic effects of coronavirus pandemic on the global economy by pitching its searchlights on the demand and supply shocks. The study employed Vector Autoregression (VAR) technique and Granger causality test; the Granger causality test revealed that COVID-19 pandemic does not trigger change in regional stock markets and commodity prices within these regions; except for the price of natural gas which changed as a result of the COVID19 pandemic in Europe. Besides the EURONEXT market in Eastern Mediterranean region, the impulse response shows that other regional stock markets responded positively to shocks in daily report of COVID-19 confirmed cases. The study concludes that within the study period, the HSBC’s stock index was the worst-hit. Economies must embrace aggressive efforts at developing COVID19 vaccine as well as coordinated policy measures at increasing the stock market pause above 15 minutes whenever stock prices fall below the lower bound threshold.